2006
DOI: 10.1631/jzus.2006.b0357
|View full text |Cite
|
Sign up to set email alerts
|

Inter-and intra-hemispheric EEG coherence in patients with mild cognitive impairment at rest and during working memory task

Abstract: Abstract:Objective: To assess functional relationship by calculating inter-and intra-hemispheric electroencephalography (EEG) coherence at rest and during a working memory task of patients with mild cognitive impairment (MCI). Methods: The sample consisted of 69 subjects: 35 patients (n=17 males, n=18 females; 52~71 years old) and 34 normal controls (n=17 males, n=17 females; 51~63 years old). Mini-mental state examination (MMSE) of two groups revealed that the scores of MCI patients did not differ significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 13 publications
4
42
1
Order By: Relevance
“…These findings are in agreement with many studies which employed cognitive tasks in the MCI population (Pijnenburg et al 2004;Jiang 2005;Jiang and Zheng 2006;Bajo et al 2010). In the alpha band, however, MCIs were desynchronized during the task.…”
Section: Control Group Vs MCI Groupsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are in agreement with many studies which employed cognitive tasks in the MCI population (Pijnenburg et al 2004;Jiang 2005;Jiang and Zheng 2006;Bajo et al 2010). In the alpha band, however, MCIs were desynchronized during the task.…”
Section: Control Group Vs MCI Groupsupporting
confidence: 92%
“…By contrast, most task studies found an increased synchronization in MCIs when compared to healthy people during a cognitive task (i.e., memory task) (Pijnenburg et al 2004;Jiang 2005;Zheng et al 2007;Bajo et al 2010). For instance, Jiang and Zheng (2006) reported a higher inter-and intrahemispheric EEG coherence in MCI in a working memory task. Bajo et al (2010) found higher interhemispheric synchronization likelihood in MCI between left and right temporo-frontal sensors in most frequency bands during a short-term memory task and higher connectivity for those that later on developed dementia (Bajo et al 2012).…”
Section: Introductionmentioning
confidence: 89%
“…Patterns of high coherence between EEG signals recorded at different scalp sites have a functional significance because they are correlated with different kinds of cognitive information processing, like memory, language, concept retrieval, and music processing (sarnthein et al 1998;Weiss et al 1999;Weiss et al 1998;Weiss and Rappelsberger 2000). Most important for the purpose of the present study is that group differences in coherence levels have been linked with levels of cognitive ability (Jiang and Zheng 2006;Deeny et al 2009). hence, changes in EEG coherence as a function of acute exercise and fitness may be an important mechanism underlying the beneficial effects of exercise on cognitive performance.…”
mentioning
confidence: 71%
“…In some studies that investigate working memory tasks (Jiang, 2005a,b;Jiang & Zheng, 2006) or probable-MCI subjects , an increase of EEG synchrony was observed. This inverse effect is often interpreted as the result of a compensatory mechanism in the brain.…”
Section: Discussionmentioning
confidence: 99%